Perlindungan Hukum Terhadap Pasien Dalam Menyampaikan Keluhan Pelayanan Kesehatan di Rumah Sakit Melalui Media Massa - Adi Sakti Setionegoro (Universitas Palangka Raya, 2024)
Legal protection aims to provide legal certainty to the parties involved in a legal action. This study aims to identify the laws governing the rights of patients as well as the level of alignment between the applicable legal regulations related to legal protection of patients in voicing complaints related to health services through the mass media. This study is normative or doctrinal descriptive, which aims to analyze the existence of legal truth related to the issue of legal protection of patients in submitting complaints of health services in hospitals through the mass media. The data sources used include primary and secondary legal materials, using data collection techniques in the form of document and literature studies. The results showed that the right of patients to obtain legal protection has been regulated in the legislation. Specifically, the legal protection of patients in submitting complaints related to health services in hospitals through the mass media is regulated in Law No. 44 of 2009 concerning hospitals. However, in its implementation, there is a discrepancy between the provisions contained in the hospital Law and Law No. 11 of 2008 concerning information and electronic transactions, especially related to articles concerning acts of insult and/or defamation. In the context of horizontal synchronization between the two laws, by applying the principle of Lex specialist derogat legi generalis legislation, it can be concluded that the hospital Law is specific because it emphasizes more on the legal relationship between patients and health workers, while the ITE Law is general because it regulates electronic transactions in various aspects, including those related to crime. Therefore, the application of the ITE Law in the context of the legal relationship of patients and health workers in hospitals is considered inappropriate. In this study, the ITE Law is considered to have uncertainty, multi-interpretation, and reduces the right to freedom of expression, so that amendments are needed to provide clarity in the protection of patients ' rights.